An integrated method to produce fermented liquid feed and biologically modified biochar as cadmium adsorbents using corn stalks. (15th May 2021) - Tao, Qi; Li, Bing; Chen, Yixuan; Zhao, Junwen; Li, Qiquan; Chen, Yulan; Peng, Quanhui; Yuan, Shu; Li, Huanxiu; Huang, Rong; Wang, Changquan
Graphical abstract: Highlights: A new concept for utilization corn stalk by coupling anaerobic fermentation and pyrolysis. An anaerobic fermentation step was used to further ferment corn stalk silage. Fermented liquid feed was prepared by spontaneously fermentation. Biochar derived from non-fermented residue showed improved physic-chemical property. Biologically modified biochar is an effective adsorbent for Cd removal from water. Abstract: The recycling of agricultural waste is a global challenge to the sustainable development of agriculture. By using corn stalks, we studied the feasibility of combining anaerobic fermentation and pyrolysis processes to produce both fermentated liquid feed and biologically modified biocharas cadmium adsorbents. Anaerobic ensiling enhanced the biodegradation of corn stalks by increasing crude protein and reducing fiber contents. After 24-h anaerobic fermentation, corn stalks silage was decomposed into the liquid filtrate and non-fermented residue. Fermented liquid feed (FLF) was prepared by storing feed and liquid filtrate (1:4.0, wt/wt) in a closed tank at 20 °C for 4 days, which showed desired properties (pH < 4.5, lactic acid bacteria greater than 9.0 lg cfu g −1, lactic acid greater than 100 mmol L -1 ). The non-fermented residue was pyrolyzed at 500 °C to prepare biologically modified biochar (BCB24). In comparison with pristine biochar produced from corn stalks (CB), anaerobic ensiling and anaerobic fermentation significantly increased the surface area, oxygen-containing functional groups, as well as mineral components in BCB24. The maximum sorption capacity of Cd(II) for BCB24 was 2.1 times of CB, suggesting that BCB24 is an effective adsorbent for Cd(II) removal from water. Our results indicated that coupling anaerobic fermentation and pyrolysis technology can significantly improve the efficiency of corn stalks recycling.